2014
DOI: 10.1074/jbc.m114.573287
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Versican-V1 Proteoglycan Processing by the Metalloproteinase ADAMTS5

Abstract: Background:The mechanisms of versican proteolysis by ADAMTS proteases are unknown. Results: The ADAMTS5 ancillary domain and specific chondroitin sulfate chains of versican are required for proteolysis. Conclusion: Docking between the ADAMTS5 ancillary domain and CS chains is a major mechanism underlying versican proteolysis. Proteolysis by ADAMTS1 has a similar requirement for GAG chains. Significance: The findings suggest strategies for blocking versican cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 70 publications
4
58
0
Order By: Relevance
“…As ADAMTS1 and ADAMTS5 are required for processing the proteoglycan versican during cardiac development, we next examined versican processing using antibodies to stain for total versican (intact and cleaved) and cleaved versican (DPEAAE neoepitope) only [ 15 , 23 ]. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ADAMTS1 and ADAMTS5 are required for processing the proteoglycan versican during cardiac development, we next examined versican processing using antibodies to stain for total versican (intact and cleaved) and cleaved versican (DPEAAE neoepitope) only [ 15 , 23 ]. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to changes in BMP and MAPK signaling, we detected changes in the level of proteases known to remodel the matrix as well as changes in the abundance of certain matrix proteins. Decreases in ADAMTS1 and ADAMTS5, both of which are known to cleave versican [ 15 , 16 , 23 ], are likely responsible for decreased versican cleavage seen in the developing valves of Galnt1 nulls. As versican remodeling is required for proper cardiac development [ 15 , 16 ], these changes likely contribute to the valve phenotypes observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in several EOC cell lines, including SKOV3 and OVCAR3, V2 isoform is not expressed (37). In addition, V1 isoform can be processed into smaller fragments (40). Thus, it is possible that miR-590-3p and FOXA2 regulate the expression of V1, and possibly V0.…”
Section: Discussionmentioning
confidence: 99%
“…for 1 hour at room temperature, and stained with antibodies against versican (anti-VC), which detects intact and cleaved versican (cleavage at the E 441 -A 442 peptide bond; V1 isoform enumeration) (44), and aggrecan (polyclonal AB1031, and mouse monoclonal MCA1454G). Rabbit polyclonal antibodies against an ADAMTS protease-generated aggrecan neoepitope (NITEGE 393 ) and versican neoepitope (DPEAAE 441 ; V1 enumeration) were used to localize aggrecan and versican cleavage, respectively.…”
Section: Methodsmentioning
confidence: 99%